2017
DOI: 10.1177/0969141317733771
|View full text |Cite
|
Sign up to set email alerts
|

Lower attendance rates in immigrant versus non-immigrant women in the Norwegian Breast Cancer Screening Programme

Abstract: Objective: The Norwegian Breast Cancer Screening Programme invites women aged 50-69 to biennial mammographic screening. Although 84% of invited women have attended at least once, attendance rates vary across the country. We investigated attendance rates among various immigrant groups compared with non-immigrants in the programme.Methods: There were 4,053,691 invitations sent to 885,979 women between 1996 and 2015. Using individual level population-based data from the Cancer Registry and Statistics Norway, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
57
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 28 publications
3
57
1
1
Order By: Relevance
“…Income level of the source country does not completely explain the patterns observed in our study as for example, South Korea showed a gradual increase in participation with duration of residence in Canada, similar to Indian or CMHT immigrants. Among studies that have reported screening rates for immigrants by region or country of birth, there are similarities to our findings of lower rates of screening among women from Eastern European/Central Asian, East Asian, and South Asian countries 26, 30…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Income level of the source country does not completely explain the patterns observed in our study as for example, South Korea showed a gradual increase in participation with duration of residence in Canada, similar to Indian or CMHT immigrants. Among studies that have reported screening rates for immigrants by region or country of birth, there are similarities to our findings of lower rates of screening among women from Eastern European/Central Asian, East Asian, and South Asian countries 26, 30…”
Section: Discussionsupporting
confidence: 84%
“…Acknowledging the challenges with comparing studies, findings have generally reported that screening rates among immigrant populations are lower than those among nonimmigrants. Among these studies, several have further assessed and reported a similar positive association between duration of residence in the adopted country and screening participation 26, 30, 31. A recent population‐based study from Norway reported that participation rates rose much more quickly with years of residence in Norway for women who immigrated from high‐income countries compared to those that immigrated from middle‐ or low‐income countries.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…4,29 At the individual level, behavioural explanations, like improved language skills or knowledge about the healthcare system, might be relevant. 7,8 Despite this, our analysis did not detect differences in breast cancer survival between non-Western immigrants and Norwegians, and when we condition on stage at diagnosis, breast cancer survival was potentially even better for non-Western immigrants. Social networks of immigrant populations might also develop over time and contribute to improved healthcare in the groups with long residence time.…”
Section: Discussionmentioning
confidence: 64%
“…6 A previous study, investigating cancer stage distribution in immigrants compared to the Norwegian host population, showed that non-Western women had higher risk of being diagnosed with a more advanced stage of breast cancer. 8,9 The low screening attendance and advanced breast cancer stage distribution reported for non-Western immigrants may contribute to poor cancer survival. 8,9 The low screening attendance and advanced breast cancer stage distribution reported for non-Western immigrants may contribute to poor cancer survival.…”
mentioning
confidence: 99%